2009
DOI: 10.1507/endocrj.k09e-073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of TSH Receptor and Gs.ALPHA. Mutations in 45 Autonomously Functioning Thyroid Nodules in Japan

Abstract: Abstract. Somatic mutations of the thyrotropin receptor (TSHR) gene and the gene encoding the α subunit of the stimulatory GTP-binding protein (Gsα) are the main cause for autonomously functioning thyroid nodules (AFTN) in iodine-deficient regions of the world. In iodine-sufficient regions, including Japan, the genetic relevance of AFTN is unclear. In a series of 45 Japanese subjects with AFTN, exons 9 and 10 of the TSHR and exons 7-10 of Gsα, where the activating mutations have been found, were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
(48 reference statements)
5
22
0
Order By: Relevance
“…However, a later detailed study of 134 nodules from 50 hyperthyroid cats found ten missense mutations, of which five have previously been associated with human hyperthyroidism (Watson et al 2005). The most common TSHR mutation detected in cats is Met452-Thr (a substitution of methionine by threonine), which is analogous to the human mutation Met453-Thr observed in sporadic human nodular goiter , Nishihara et al 2009). In addition, GNAS mutations have also been documented in four of ten hyperthyroid cats examined (Peeters et al 2002).…”
Section: Figurementioning
confidence: 98%
“…However, a later detailed study of 134 nodules from 50 hyperthyroid cats found ten missense mutations, of which five have previously been associated with human hyperthyroidism (Watson et al 2005). The most common TSHR mutation detected in cats is Met452-Thr (a substitution of methionine by threonine), which is analogous to the human mutation Met453-Thr observed in sporadic human nodular goiter , Nishihara et al 2009). In addition, GNAS mutations have also been documented in four of ten hyperthyroid cats examined (Peeters et al 2002).…”
Section: Figurementioning
confidence: 98%
“…Although the prevalence of autonomous thyroid nodules causing hyperthyroidism is very low in Japan, where iodine intake is sufficient, the frequency of constitutively active somatic TSHR mutations in patients with this condition is similar to that in iodine-insufficient areas (32,33). In another family with hereditary nonautoimmune hyperthyroidism in Japan, the hyperthyroidism in the affected members was well controlled with inorganic iodine (17).…”
Section: Discussionmentioning
confidence: 97%
“…Iodine deficiency is a wellknown risk factor for nodular thyroid disease [14,15]. Although the frequencies of TSHR and GNAS mutations in Japan had been believed to be much lower than those observed in iodine-deficient areas [7,8], a recent report suggests that the frequencies as well as the hot spots of TSHR and GNAS mutations are similar to those in iodine-deficient regions [9]. In our series, TSHR mutations were detected in 5 cases out of 8 cases (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In iodine-deficient region, either codon 281 or 568 mutations are found in 6 out of 52 TSHR mutations (11.5%), including S281N in 1 case, S281T in 1 case and I568T in 4 cases [10]. A report from Japan, iodine sufficient region, these mutations are found in 2 out of 22 TSHR mutations (9.1%), including S281N in 1 case and I568T in 1 case [9].…”
Section: Casementioning
confidence: 90%
See 1 more Smart Citation